Negotiating Notions of Self, Culture, and Curriculum throughout Graduate School: One Student's Reflexive Explorations - Christina Skorobohacz (Canadian Society for Studies in Education, 2014)
Inspired by an autoethnographic mode of inquiry, I attempt to make sense of my experiences during graduate school by exploring critical incidents that have propelled me to reconstruct new visions of myself as a scholar and to adopt flexible understandings of curricula in higher education. I articulate several significant experiences involving my ongoing negotiations of self, culture, and curriculum throughout graduate studies. Utilizing a poststructuralist lens of analysis I take up these moments of tension, by asking myself a series of Deleuzian inspired questions (Williams, 2005), which prompt reflexive thought. These questions may help other graduate students to reconcile contradictions they encounter throughout their graduate education, while striving to identify productive visions for themselves as scholars and to adopt open-mindedness towards different perspectives.